Matt coating material as well as preparation method and application thereof
By using matte coating materials with specific components, the problem of poor dissolution performance of silicon powder in traditional matte electrochemical aluminum processes is solved, and low gloss, delicate surface and excellent matte effect is achieved, which is suitable for holographic hot stamping technology.
Patent Information
- Application Number
- CN202411483435.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
In the traditional matte electrochemical aluminum process, the dissolution performance of silicon powder is not ideal, resulting in rough surface and high glossiness of the coating, failing to achieve the ideal matte decorative effect, and affecting the anti-counterfeiting effect.
Matte coating materials using hydroxyacrylic polymer resins, dispersants, isocyanate curing agents, vapor phase silica and drying agents, and through specific component ratios and process steps, they can form excellent matte effect and resistance. Frictional coating.
It achieves low gloss, delicate surface, excellent matte effect and friction resistance, while improving the adhesion fastness and solvent resistance of the coating, and is suitable for holographic hot stamping technology.
Smart Images

Figure BDA0005098093060000051 
Figure BDA0005098093060000052 
Figure BDA0005098093060000061
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coating technology, in particular to the field of IPC C09D175, and more specifically to a matte coating material and a preparation method and application thereof. Background Art
[0002] In recent years, matte electroplated aluminum has gradually gained favor in the market for its unique matte effect, and has become a new popular choice in the market. Traditional matte electroplated aluminum is formed by adding silicon powder to the coloring layer to form a coating surface with a certain hiding power, blocking the light reflected by the aluminum-plated layer, causing diffuse reflection of light on the upper film surface to play a matte effect. Therefore, after hot stamping, the matte holographic electroplated aluminum produced by this process still has a high gloss on the printed surface, but the metallic feel is weak, and the envisioned matte decorative beautification effect is not achieved. At the same time, this process also has more serious appearance defects: the solubility of silicon powder in resin coating is not ideal, and when the coating is formed, its surface often appears not delicate enough. Visually, the raised silicon powder particles can be clearly seen, which not only greatly reduces the aesthetics of the packaging, but is also likely to affect the realization of its anti-counterfeiting effect.
[0003] Chinese invention patent CN103849308A discloses a new type of matte electrochemical aluminum hot stamping foil coating, which is prepared from the following materials in a certain weight ratio: 20-40 parts of acrylic modified polyurethane, 2-5 parts of tributyl citrate, 1-10 parts of pure acrylate, 10-20 parts of benzoic acid diallyl resin, 30-60 parts of butanone, 5-20 parts of butyl ester, and 10-20 parts of matte powder. The new type of matte electrochemical aluminum hot stamping foil coating obtained by the invention has a simple production process and is conducive to large-scale production. The electrochemical aluminum hot stamping foil produced by it has low gloss, but it is not suitable for holographic hot stamping technology. Summary of the invention
[0004] The first aspect of the present invention provides a matte coating material, the components of which include matte varnish, a first solvent and a drying agent; the components of the matte varnish include: hydroxy acrylic polymer resin, a dispersant, an isocyanate curing agent, fumed silica and a second solvent.
[0005] The hydroxyl value of the hydroxy acrylic polymer resin is 20-100 mg KOH / g, the intrinsic viscosity at 25° C. is 0.1-0.3 dL / g, and the glass transition temperature is 30-80° C.
[0006] Preferably, the hydroxyl value of the hydroxy acrylic polymer resin is 20-100 mg KOH / g, the intrinsic viscosity at 25°C is 0.1-0.2 dL / g, and the glass transition temperature is 40-70°C.
[0007] The hydroxylated acrylic polymer resin comprises a first hydroxylated acrylic polymer resin having a hydroxyl value of 50-100 mg KOH / g and a second hydroxylated acrylic polymer resin having a hydroxyl value of 20-50 mg KOH / g, wherein the weight ratio of the first hydroxylated acrylic polymer resin to the second hydroxylated acrylic polymer resin is (1-3):(3-1).
[0008] Preferably, the weight ratio of the first hydroxylated acrylic polymer resin to the second hydroxylated acrylic polymer resin is (1-2):(2-1).
[0009] More preferably, the weight ratio of the first hydroxylated acrylic polymer resin to the second hydroxylated acrylic polymer resin is (1-1.5):(1.5-1).
[0010] More preferably, the weight ratio of the first hydroxylated acrylic polymer resin to the second hydroxylated acrylic polymer resin is 1:1.
[0011] The first solvent and the second solvent both include at least one of butanone, ethyl acetate, n-propyl acetate, propylene glycol methyl ether, dimethyl succinate, dimethyl glutarate, methyl butanone, methyl isobutyl ketone and cyclohexanone.
[0012] The first solvent and the second solvent both include at least one of butanone, ethyl acetate, and n-propyl acetate.
[0013] Preferably, the second solvent comprises butanone and n-propyl acetate, and the weight ratio of butanone to n-propyl acetate is 1:(0.5-1.5).
[0014] Further preferably, the second solvent comprises butanone and n-propyl acetate, and the weight ratio of butanone to n-propyl acetate is 1:(0.9-1.3).
[0015] Preferably, the isocyanate curing agent comprises aliphatic polyisocyanate.
[0016] Preferably, the NCO content of the aliphatic polyisocyanate is 20-30 wt % (DIN EN ISO 11909).
[0017] More preferably, the NCO content of the aliphatic polyisocyanate is 20-25 wt %.
[0018] Preferably, the drier comprises an organotin drier.
[0019] The D50 particle size of the fumed silica is 10-80 microns.
[0020] Preferably, the D50 particle size of the fumed silica is 10-50 microns.
[0021] Further preferably, the D50 particle size of the fumed silica is 10-30 microns.
[0022] More preferably, the D50 particle size of the fumed silica is 10-20 microns.
[0023] The amount of the fumed silica added to the matte varnish is 5-15wt%.
[0024] Preferably, the amount of the fumed silica added to the matte varnish is 8-12 wt %.
[0025] Further preferably, the amount of the fumed silica added to the matte varnish is 8 wt %.
[0026] The amine value of the dispersant is 5-30 mg KOH / g.
[0027] Preferably, the amine value of the dispersant is 5-25 mg KOH / g.
[0028] Preferably, the dispersant is added in an amount of 0.1-1 wt % in the matte varnish.
[0029] Preferably, the dispersant is added in an amount of 0.5 wt % in the matte varnish.
[0030] Preferably, the dispersant comprises one of the following types: at least one of BYK-164, BYK-167, BYK-170, BYK-2164 and BYK-163.
[0031] The amount of the drying agent added to the matte coating material is 0.05-3wt%, and the weight ratio of the drying agent to the isocyanate curing agent is (0.05-0.15): (5-15).
[0032] Preferably, the amount of the drying agent added to the matte coating material is 0.05-0.15 wt %, and the weight ratio of the drying agent to the isocyanate curing agent is (0.05-0.15): (5-12).
[0033] Further preferably, the weight ratio of the drying agent to the isocyanate curing agent is 0.1:(2.8-22.4).
[0034] More preferably, the weight ratio of the drying agent to the isocyanate curing agent is 0.1:5.6.
[0035] Further preferably, the dispersant includes at least one of BYK-167, BYK-170, and BYK-2164.
[0036] The applicant has found that the film-forming properties of a hydroxyl acrylic polymer resin can be improved by selecting a hydroxyl value of 20-100 mg KOH / g, an intrinsic viscosity of 0.1-0.3 dL / g at 25°C, and a glass transition temperature of 30-80°C. This may be because the reaction byproducts, oligomers and residual monomers, are reduced, and the reaction efficiency is improved, thereby providing better chemical resistance and hardness. Further research has found that by selecting a first hydroxyl acrylic polymer resin with a hydroxyl value of 50-100 mg KOH / g and a second hydroxyl acrylic polymer resin with a hydroxyl value of 20-50 mg KOH / g, and the weight ratio of the first hydroxyl acrylic polymer resin to the second hydroxyl acrylic polymer resin is (1-3): (3-1), the viscosity of the system can be controlled to be 25-30s. This may be because the ratio of resins with different molecular weights has different effects on the viscosity of the coating system of the present application. When the amount of resin with a large molecular weight added is too high, the viscosity is too high and cannot meet the requirements.
[0037] A second aspect of the present invention provides a method for preparing a matte coating material, comprising the following steps:
[0038] S1, mixing a hydroxy acrylic polymer resin with a second solvent, adding a dispersant and fumed silica, and then adding an isocyanate curing agent to obtain a matte varnish;
[0039] S2, mix the first solvent and the drying agent evenly, add the matte varnish, and stir evenly to obtain.
[0040] Preferably, the method comprises the following steps:
[0041] S1, add the second solvent, start stirring, set the speed at 300-800rpm, add hydroxy acrylic polymer resin, raise the solution to 40-60℃, stir at a stirring speed of 1200-2000rpm for 1-3h until the resin is fully dissolved, turn off the heating, and reduce the stirring speed to 300-800rpm. Add dispersant and add fumed silica, stir for 3-15min, increase the speed to 2000-2800rpm after the fumed silica powder is fully wetted, and stir for 10-40min; add isocyanate curing agent, stir for 10-30min, and filter the material with a 100-500 mesh filter bag;
[0042] S2, add the first solvent, start stirring, set the speed at 300-800rpm. Add the drying agent, stir for 3-15min to fully mix the solvent and the additive, increase the stirring speed to 800-1600rpm, add matte varnish, stir for 10-30min, filter the material with a 100-500 mesh filter bag, and obtain.
[0043] A third aspect of the present invention provides an application of a matte coating material, which is applied to the process of preparing electrochemical aluminum using holographic hot stamping technology.
[0044] Beneficial Effects
[0045] 1. Selecting a hydroxyl acrylic polymer resin with a hydroxyl value of 20-100 mg KOH / g, an intrinsic viscosity of 0.1-0.3 dL / g at 25°C, and a glass transition temperature of 30-80°C can improve film-forming properties.
[0046] 2. Select the first hydroxyl acrylic polymer resin with a hydroxyl value of 50-100 mg KOH / g and the second hydroxyl acrylic polymer resin with a hydroxyl value of 20-50
[0047] The first hydroxy acrylic polymer resin has a weight ratio of (1-3): (3-1) to the second hydroxy acrylic polymer resin, and the viscosity of the system can be controlled at 25-30s to provide processing performance.
[0048] 3. The D50 particle size of fumed silica is 10-80 microns, which can increase the amount of fumed silica added to matte varnish to 5-15wt%, and the viscosity is 25-30s at 25°C, while making the coating have excellent matte effect (60° gloss ≤ 20) and abrasion resistance.
[0049] 4. The amount of the drying agent added to the matte coating material is 0.05-0.15wt%, and the weight ratio of the drying agent to the isocyanate curing agent is (0.05-0.15): (5-12), which can improve the solvent resistance and adhesion of the coating, and the activation period is not less than 2h.
[0050] 5. The amine value of the dispersant is 5-30 mg KOH / g, which can reduce the viscosity of the resin system, improve the gloss, color intensity, transparency and hiding power of the coating, effectively prevent the accumulation and flocculation of the pigment, make the coating fineness no more than 25 microns, and at the same time make the system surface tension greater than 38 dynes, thereby improving the processing performance.
[0051] 6. The weight ratio of the drying agent to the isocyanate curing agent is 0.1:(2.8-22.4), and the activation period of the coating can be greater than 6 hours, which meets the process requirements for preparing electrochemical aluminum by holographic hot stamping technology.
[0052] 7. The coating material prepared in this application is applied to electrochemical aluminum to protect its color layer and reflect light. DETAILED DESCRIPTION
[0053] Examples 1-18
[0054] A matte coating material, comprising matte varnish, a first solvent and a drying agent; the matte varnish comprises: a hydroxylated acrylic polymer resin, a dispersant, an isocyanate curing agent, fumed silica and a second solvent; the amounts of the components in parts by weight are as shown in Table 1 (matte coating material) and Table 2 (matte varnish).
[0055] The drying agent is an organic tin drying agent, model: T12, purchased from Guangdong Sandingjia New Material Technology Co., Ltd.
[0056] Table 1
[0057]
[0058] Table 2
[0059]
[0060]
[0061] A method for preparing the matte coating material according to claim 1, comprising the following steps:
[0062] S1, add the second solvent to the stirring kettle, start stirring at a constant speed of 500rpm, add hydroxy acrylic polymer resin, raise the solution to 50°C, stir at a stirring speed of 1500rpm for 2h until the resin is fully dissolved, turn off the heating, and reduce the stirring speed to 500rpm. Add dispersant and add fumed silica, stir for 5min, increase the speed to 2500rpm after the fumed silica powder is fully wetted, and stir for 30min; add isocyanate curing agent, stir for 15min, and filter the material with a 200-mesh filter bag;
[0063] S2, add the first solvent to the stirring kettle, start stirring at a constant speed of 500rpm. Add the drying agent, stir for 5min to fully mix the solvent and the additive, increase the stirring speed to 1000rpm, add matte varnish, stir for 15min, and filter the material with a 200-mesh filter bag to obtain.
[0064] Performance testing methods and data
[0065] The coating materials prepared in Examples 1-18 were respectively prepared into strips: 6 cm × 60 cm PET film (biaxially oriented polyester film PET, model: 1310, thickness 12 μm, purchased from Foshan DuPont Hongji Film Co., Ltd.) strips were cut, stains and dust on the surface of the film were gently wiped off with cotton wool soaked in anhydrous ethanol, and dried under natural conditions.
[0066] The corona-treated film strips were sampled by the IGT F1 device to simulate the printing process. The plastic film was first fixed on the track of the printing press, and then an appropriate amount of matte varnish was added between the anilox roller and the scraper, and it was ensured that there were no bubbles in the varnish. After starting the machine, every time the anilox roller rotated two weeks, the plate cylinder completed a rotation, and the printing track moved forward. Every time the plate cylinder completed a rotation, the varnish was transferred from the anilox roller to the flexible printing plate, and further transferred to the plastic film, which marked the end of the simulated printing process. The effective strip length was 50 cm. Subsequently, the strips were placed in an oven set at 135°C for curing for 10 seconds to complete the sample preparation process.
[0067] 1. 60° gloss test: The gloss meter (YG268, 3nh Shenzhen Sanenshi Technology Co., Ltd.) measures the intensity of these reflected lights to obtain the glossiness of the object surface. During the measurement, the light is irradiated to the surface of the object at a certain angle, and the reflected light enters the detector, which then converts the intensity of the reflected light into an electrical signal, and the glossiness value is calculated. As shown in Table 3, the glossiness / mattness of the 18 examples can meet the mattness requirements of this project (glossiness ≤ 20).
[0068] Table 3
[0069] Example Gloss (60°) Example Gloss (60°) 1 18.2 10 19.1 2 17.8 11 18.4 3 18.4 12 17.8 4 18.6 13 18.4 5 19.0 14 18.5 6 18.5 15 18.6 7 17.8 16 18.2 8 18.2 17 17.7 9 18.3 18 19.1
[0070] 2. Fineness measurement: Scraper fineness meter (Dedu Instrument Co., Ltd.), as shown in Table 4, the paint fineness is no more than 25 microns.
[0071] Table 4
[0072] Example Fineness (micrometer) Example Fineness (micrometer) 1 22 10 23 2 23 11 22 3 20 12 21 4 22 13 23 5 21 14 24 6 23 15 21 7 22 16 22 8 21 17 22 9 23 18 22
[0073] 3. Viscosity test(s): 25℃, rotational viscometer, No. 4 (Pushen Testing Instruments (Shanghai) Co., Ltd.). As shown in Table 5, the ratio of resins with different molecular weights has the greatest influence on the viscosity of the coating. When the addition amount of resin with large molecular weight reaches 9wt%, the coating viscosity of the coating is significantly improved, meeting the project requirements. When the addition amount of resin with large molecular weight reaches 12wt%, the viscosity is too high and cannot meet the requirements.
[0074] When the ratio of 261 to 262 resin is 2:1, the viscosity of the coating is low; when the ratio of 261 to 262 resin is 1:1, the viscosity of the coating meets the project requirements; when the ratio of 261 to 262 resin is 1:, the viscosity of the coating is low.
[0075] In the experiment, the proportion of the resin with lower molecular weight (BM261) was high, resulting in low viscosity in Examples 1, 7, and 13. The proportion of the resin with higher molecular weight (BM262) was high, resulting in high viscosity in Examples 3, 9, and 15. The viscosity of the remaining examples met the project requirements (25-30s).
[0076] Example Viscosity(s) Example Viscosity(s) 1 18.2 10 27.6 2 27.5 11 26.8 3 35.2 12 27.2 4 26.6 13 19.3 5 27.4 14 27.2 6 28.2 15 34.5 7 19.7 16 26.8 8 26.8 17 25.9 9 33.8 18 27.5
[0077] 4. Adhesion fastness (grade) measurement: peel force tester, SHK-Example 101, Suzhou Jianzhuo Instrument Technology Co., Ltd. As shown in Table 6, the amount of drying agent added and the amount of isocyanate curing agent added both have a great influence on the adhesion fastness of the coating. When the amount of drying agent added reaches 0.1%, the adhesion fastness of the coating is significantly improved; when the amount of isocyanate curing agent added reaches 7%, the adhesion fastness of the coating is significantly improved. The comparative tests of Examples 1-6, 7-12, 13-18 prove the influence of the amount of drying agent added on the adhesion fastness of the coating. The greater the amount of drying agent added, the faster the coating reacts when cured by heat, and the higher the adhesion fastness of the coating. The three groups of tests of Examples 2, 4, 5, 6 and 8, 10, 11, 12 and 14, 16, 17, 18 prove the influence of the amount of isocyanate curing agent added on the adhesion fastness of the coating. The higher the amount of isocyanate curing agent added, the higher the adhesion fastness.
[0078] Table 6
[0079] Example Adhesion fastness (grade) Example Adhesion fastness (grade) 1 2 10 2 2 2 11 1 3 2 12 1 4 3 13 1 5 2 14 1 6 2 15 1 7 1 16 2 8 1 17 1 9 1 18 1
[0080] 5. Friction resistance (grade) test: The principle of measuring the friction resistance of the coating is to use a friction tester (MH305, Xinyu Yian) to perform a friction test on the coating. Use a friction head to rub the surface of the coating back and forth, and record the number of frictions or the friction distance required for the coating to be worn to a certain degree, so as to evaluate the friction resistance of the coating. As shown in Table 7, the amount of drying agent added has a greater effect on the friction resistance of the coating. When the amount of drying agent added reaches 0.1%, the friction resistance of the coating is significantly improved. The comparative tests of Examples 1-6, 7-12, and 13-18 prove the effect of the amount of drying agent added on the friction resistance of the coating. The greater the amount of drying agent added, the faster the coating reacts when heat-cured, and the higher the friction resistance of the coating.
[0081] Table 7
[0082] Example Wear resistance (grade) Example Wear resistance (grade) 1 4 10 5 2 4 11 5 3 4 12 5 4 4 13 5 5 4 14 5 6 4 15 5 7 5 16 5 8 5 17 5 9 5 18 5
[0083] 6. Solvent resistance test: The test solvent is butanone. As shown in Table 8, the amount of drying agent added has a great influence on the solvent resistance of the coating. When the amount of drying agent added reaches 0.1%, the solvent resistance of the coating is significantly improved. The comparative test of Examples 1-6, 7-12, and 13-18 proves the influence of the amount of drying agent added on the solvent resistance of the coating. The greater the amount of drying agent added, the faster the coating reacts when cured by heat, and the better the solvent resistance of the coating.
[0084] Table 8
[0085] Example Solvent resistance (grade) Example Solvent resistance (grade) 1 4 10 5 2 4 11 5 3 4 12 5 4 4 13 5 5 4 14 5 6 4 15 5 7 5 16 5 8 5 17 5 9 5 18 5
[0086] 7. Coating uniformity test: This experiment evaluates the uniformity of coating thickness, color, gloss, etc. by observing the uniformity of coating and coating defects in a color matching box (standard light source). For coatings with good coating uniformity, the thickness, color, gloss, etc. should remain consistent in all areas of the coating surface without obvious fluctuations or differences. As shown in Table 9, the coating uniformity is divided into levels 1-6, and the larger the number, the worse the uniformity. In the experiment, the coating uniformity of the 18 examples all met the project indicator requirements (level 1).
[0087] Table 9
[0088] Example Uniformity (grade) Example Uniformity (grade) 1 1 10 1 2 1 11 1 3 1 12 1 4 1 13 1 5 1 14 1 6 1 15 1 7 1 16 1 8 1 17 1 9 1 18 1
[0089] 8. Surface tension measurement: Use a dyne pen to draw the largest uniform line on the coating surface to determine the surface tension of the coating. As shown in Table 10, the surface tension of the 18 examples is 42 dynes, which meets the requirement of 38 dynes or more of the project.
[0090] Table 10
[0091] Example Surface tension (dynes) Example Surface tension (dynes) 1 42 10 42 2 42 11 42 3 42 12 42 4 42 13 42 5 42 14 42 6 42 15 42 7 42 16 42 8 42 17 42 9 42 18 42
[0092] 9. Determination of open time (activation period): Apply the coating on the test plate and record the time from the fluid state to the time when the coating cannot be leveled again. As shown in Table 11, the amount of drying agent added and the amount of isocyanate curing agent added have a great influence on the open time (activation period) of the coating. When the amount of drying agent added reaches 0.1%, the open time (activation period) of the coating is significantly shortened. When the amount of drying agent added reaches 0.15%, the open time is less than 6 hours; when the amount of isocyanate curing agent added reaches 7%, the open time of the coating is significantly shortened.
[0093] The comparative tests of Examples 1-6, 7-12 and 13-18 prove the influence of the amount of drying agent added on the open time of the coating. The greater the amount of drying agent added, the shorter the open time of the coating.
[0094] The three groups of experiments in Examples 2, 4, 5, 6 and 8, 10, 11, 12 and 14, 16, 17, 18 prove that the amount of isocyanate curing agent added affects the open time of the coating. The higher the amount of isocyanate curing agent added, the shorter the open time.
[0095] In the experiment, the opening time of Examples 1-10 was greater than 6 hours, which met the project requirements.
[0096] Table 11
[0097] Example Opening hours (hours) Example Opening hours (hours) 1 16 10 10 2 16 11 6 3 16 12 4 4 18 13 4 5 14 14 4 6 12 15 4 7 8 16 6 8 8 17 4 9 8 18 2
Claims
1. A matte coating material, characterized in that: The components include matte varnish, a first solvent and a drying agent; the components of the matte varnish include hydroxy acrylic polymer resin, a dispersant, an isocyanate curing agent, gas-phase silica and a second solvent.
2. The matte coating material according to claim 1, characterized in that: The hydroxyl value of the hydroxy acrylic polymer resin is 20-100 mg KOH / g, the intrinsic viscosity at 25° C. is 0.1-0.3 dL / g, and the glass transition temperature is 30-80° C.
3. The matte coating material according to claim 2, characterized in that: The hydroxylated acrylic polymer resin comprises a first hydroxylated acrylic polymer resin having a hydroxyl value of 50-100 mg KOH / g and a second hydroxylated acrylic polymer resin having a hydroxyl value of 20-50 mg KOH / g, wherein the weight ratio of the first hydroxylated acrylic polymer resin to the second hydroxylated acrylic polymer resin is (1-3):(3-1).
4. The matte coating material according to claim 3, characterized in that: The first solvent and the second solvent both include at least one of butanone, ethyl acetate, n-propyl acetate, propylene glycol methyl ether, dimethyl succinate, dimethyl glutarate, methyl butanone, methyl isobutyl ketone and cyclohexanone.
5. The matte coating material according to claim 4, characterized in that: The isocyanate curing agent includes aliphatic polyisocyanate.
6. The matte coating material according to claim 1 or 5, characterized in that: The D50 particle size of the fumed silica is 10-80 microns.
7. The matte coating material according to claim 6, characterized in that: The amine value of the dispersant is 5-30 mgKOH / g.
8. The matte coating material according to claim 1 or 7, characterized in that: The amount of the drying agent added to the matte coating material is 0.05-3wt%, and the weight ratio of the drying agent to the isocyanate curing agent is (0.05-0.15): (5-15).
9. A method for preparing the matte coating material according to claim 8, characterized in that: The following steps are involved: S1, mixing a hydroxy acrylic polymer resin with a second solvent, adding a dispersant and fumed silica, and then adding an isocyanate curing agent to obtain a matte varnish; S2, mix the first solvent and the drying agent evenly, add the matte varnish, and stir evenly to obtain.
10. An application of the matte coating material according to claim 8, characterized in that: It is used in the process of preparing electrochemical aluminum by holographic hot stamping technology.
Citation Information
Patent Citations
Water-based finish paint for polyurethane foam material
CN102775868A
Coating material and preparation method thereof
CN102850871A
Thermosetting adjustable matte gloss oil for metal printing and preparation method of thermosetting adjustable matte gloss oil
CN115322662A
Composition for matt coating decoration sheet and matt coating decoration sheet
KR1020180101032A
